Application of the New Asthma-Specific Job Exposure Matrix: A Study in Quebec Apprentice Cohort Exposed to Isocyanates - Bilge Akgündüz; Stephie Pierre; Lama Saab; Nicole Le Moual; Denyse Gautrin; Catherine Lemiere; Suarthana Eva; Hormoz Nassiri Kigloo (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: Recently, the first asthma-specific Job Exposure Matrix (JEM) was updated to occupational asthma-specific JEM (OAsJEM). Our study aimed to evaluate the association between continued exposure to isocyanates and incident work-related chest symptoms in former car-painting apprentices and to compare the associations using the first and new OAsJEMs.Methods: We used data from an inception cohort of male car-painting apprentices. Post-apprenticeship exposure to isocyanate during follow-up was evaluated using the first asthma-specific JEM (“exposed”=1 or “not exposed”=0) and the new OAsJEM (high=2, medium=1, and none=0). Association between occupation exposure to isocyanate and incidence of work-related rhinoconjunctival and chest symptoms were evaluated through cox regression models, adjusted for age, smoking, wheezing, and non-specific bronchial hyperresponsiveness. Results: The agreement between the two JEMs (exposed vs non-exposed to isocyanate) was perfect (kappa coefficient=0.946, p<0.001). There were only five subjects who were classified as non-exposed based on the first JEM, but had a medium exposure to isocyanate based on the new OAsJEM. Exposure to isocyanate increased the risk of occupational chest symptoms in the high-exposure category (hazard ratio [HR] 2.7, 95% CI 1.1 – 6.6) and the medium category (HR 2.9, 95% CI 0.3 – 30.0) compared to the reference group based on the new OAsJEM, whereas an HR of 2.5 (95% CI 1.0-6.2) was observed from the first JEM. Both JEMs yielded an inconclusive association between exposure to isocyanates and the risk for work-related rhino-conjunctivitis. Conclusion: The asthma-specific JEM and OAsJEM consistently showed that isocyanate exposure increased the risk of incident work-related chest symptoms.